The dental alloys determine the choice of composite resins to be used. - Izabela Cristina Maurício Moris; Matheus Sakuma; Adriana Cláudia Lapria Faria; Ana Paula Macedo; Ricardo Faria Ribeiro; Renata Cristina Silveira Rodrigues (Brazilian Dental Science)
Objective: The aim of the present study was to evaluate wear resistance of two composites resins against alternative alloys. Material and Methods: Fifteen stylus tips samples of composite resin were obtained for each resin Z250 and charisma (CHA). Samples were divided into three groups according to the disk of alloy to be used as antagonist: Nickel-Chromium (Ni-Cr), Cobalt- Chromium (Co-Cr) and commercially pure titanium (cp Ti). Wear tests were performed at a speed of 265 cycles/min and distance of 10mm, in a total of 40,000 cycles. Before and after wear tests, samples were weighed and had their profile designed in an optical comparator to evaluate weight and height loss, respectively. Results: For weight and height loss, wear of Z250 was lower than CHA for Co-Cr antagonist, but greater for cp Ti. CHA presents a more regular surface without cracks and similar aspect for all antagonists. Z250 showed some cracks, mainly against cp Ti and Ni-Cr. Conclusion: Within the results of the present study, it was concluded that CHA is suitable against cp Ti, and Z250 for association with Co-Cr alloy while any composite resin can be used against Ni-Cr. Keywords Composite resins; Dental alloys; Dental restoration wear.